Determining cut-off values and predictors for the Snaith–Hamilton Pleasure Scale: comparison between clinical and school settings - Yen-Chung Ho; Susan Shur-Fen Gau; Ying-Sian Wu; Chun-Hsin Chen; Jiunn-Kae Wang; Hsin-Chien Lee; Kuo-Hsuan Chung; Yi-Hang Chiu; Kah Kheng Goh; Mong-Liang Lu; Yu-Chun Lin; Pi-Chen Chang; et al. (BJPsych Open, 2024)
Background Few previous studies have established Snaith–Hamilton Pleasure Scale (SHAPS) cut-off values using receiver operating characteristic curve analysis and applied these values to compare predictors of anhedonia between clinical and nonclinical groups.